Use of the PDCA cycle and application of MILK RUN in a reverse logistics process in a food industry - de Paula, Johnatan Correia Mantay; Feroni, Rita de Cassia (Brazilian Journal of Production Engineering, 2021)
Reverse logistics has stood out within the associations as a business strategy, which in addition to supporting itself in legal and socio-environmental aspects, seeks customer satisfaction. Thus, the present study analyzed the reverse logistics in a food industry aiming to generate practical and viable solutions to the problem of dissatisfaction of the main customers of the organization, motivated by the inefficiency of the reverse processes. Therefore, the PDCA methodology was used as the central guideline in solving the proposed problem, as well as the milk run technique as the main action of the work. As a result, results are greater efficiency in the reverse logistics process, based on four main indicators: i) faster return of returns products due to faster load consolidation due to the application of the milk run; ii) reduction of reverse freight costs in the South region motivated by the negotiation carried out, mainly based on the centralization of volumes on the same carrier; iii) increase in the level of satisfaction of the organization's main customers; iv) greater reuse of the returned products due to greater agility in this reverse process.
Keywords: Reverse Logistic; PDCA; Milk Run; Customer satisfaction